2021
DOI: 10.48550/arxiv.2102.06866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Negative Samples in Instance Discriminative Self-supervised Representation Learning

Abstract: Instance discriminative self-supervised representation learning has been attracted attention thanks to its unsupervised nature and informative feature representation for downstream tasks. Self-supervised representation learning commonly uses more negative samples than the number of supervised classes in practice. However, there is an inconsistency in the existing analysis; theoretically, a large number of negative samples degrade supervised performance, while empirically, they improve the performance. We theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Along with various subject matter improvements [26-29, 8, 9], contrastive learners now provide comprehensive solutions for self-supervised learning. Despite encouraging progress, there are still many unresolved issues with contrastive learning, with the following three particularly relevant to this investigation: (i) contrastive learners need a very large number of negative samples to work well; (ii) the bias, variance, and performance tradeoffs are in debate [13,21,30]; and, crucially, (iii) there is a lack of training diagnostic tools for contrastive learning. Among these three, (i) is most concerning, as it implies training can be very expensive, while the needed massive computational resources may not be widely available.…”
Section: Introductionmentioning
confidence: 99%
“…Along with various subject matter improvements [26-29, 8, 9], contrastive learners now provide comprehensive solutions for self-supervised learning. Despite encouraging progress, there are still many unresolved issues with contrastive learning, with the following three particularly relevant to this investigation: (i) contrastive learners need a very large number of negative samples to work well; (ii) the bias, variance, and performance tradeoffs are in debate [13,21,30]; and, crucially, (iii) there is a lack of training diagnostic tools for contrastive learning. Among these three, (i) is most concerning, as it implies training can be very expensive, while the needed massive computational resources may not be widely available.…”
Section: Introductionmentioning
confidence: 99%
“…InfoNCE loss was identified to have the hardnessaware property, which is critical for optimization [64] and preventing collapse by instance de-correlation [1]. [15], [34], [36], [49], [62], [66], [69] have demonstrated that hard negative samples mining strategies can be beneficial for better performance over the baselines. Notably, [65] identified CL form alignment and uniformity of feature space which benefits downstream tasks.…”
Section: Related Workmentioning
confidence: 99%
“…In the view of optimization, the hardness-aware property puts more weight into optimizing negative pairs that have high similarities. This way is influenced by hard examples mining and has proven to be effective [4], [36], [49], [62], [66], [72].…”
Section: B Hardness-aware Property In Dimclmentioning
confidence: 99%
“…Given its empirical success, there has been significant interest in the theory of contrastive learning, from various perspectives. Most relevant to us are learning theoretic analyses [Arora et al, 2019, Tosh et al, 2021b,a, HaoChen et al, 2021, Wang et al, 2022 and their follow ups [Nozawa andSato, 2021, Ash et al, 2021]. These study the downstream linear classification performance of learned representation, by making assumptions about the data and augmentation distributions; we discuss these in more detail in Section 2.…”
Section: Related Workmentioning
confidence: 99%